P-527 Comparison of implantation rate and preimplantation genetic testing between hatching and hatched blastocysts. (30th June 2022) - Adams, T; Markle, M; Leisinger, C
Abstract: Study question: Does embryo stage, hatching versus hatched blastocyst, affect ploidy status and implantation rates (IR)? Summary answer: The embryo stage may influence ploidy status, but no correlation was made between embryo stage and IR. What is known already: It is generally accepted that hatched embryos present increased vulnerability when handled and are often selected against. The literature on this varies with some reporting that the transfer of hatched blastocysts resulted in lower pregnancy rates compared to hatching or expanded blastocysts. Other studies have found no difference in clinical outcome with the transfer of hatched blastocysts compared to other stages. Reports defining the relationship between hatched or hatching blastocysts and ploidy rates are limited. Study design, size, duration: Retrospective analysis of IR of 224 transferred euploid embryos and ploidy rate (P-Rt) of 1431 embryos produced in two IVF labs in the United States between 2019-2021. Embryos underwent assisted hatching on Day 3 and were subjected to preimplantation genetic testing (PGT) on Day 5 or Day 6 followed by vitrification. IR was defined as the presence of an intrauterine implantation sac with the detection of a fetal heartbeat on ultrasound. Participants/materials, setting, methods: Trophectoderm biopsies were evaluated by NextGen Sequencing at the same genetics laboratory (Ovation Genetics, Nashville, TN). P-Rt included the following categories: Normal (N) or euploid, Abnormal (ABN) or aneuploid, Low-Mosaic (LM), and High-Mosaic (HM). Euploid embryos were transferred in subsequent frozen embryo transfer (FET) cycles and monitored by clinical ultrasound. Chi-square statistical analysis was performed to identify potential differences (p < 0.05). Main results and the role of chance: No significant difference was observed in IR after transferring euploid hatched blastocysts compared to euploid hatching blastocysts. The IR of hatched blastocysts was 40.3% compared to 50.3% for hatching blastocysts (p = 0.21). A significant difference in ABN and HM embryos was observed according to embryo stage (p = 0.02). The ABN rate was 21.2% for hatched blastocysts compared to 28.0% for hatching blastocyst and the HM rate of hatched blastocysts was 10.3% versus hatching blastocyst at 7.5%. No significant difference in Normal and LM ploidy rates were observed according to embryo stage. The N ploidy rate of hatched blastocysts was 58.1% versus 54.4% in hatching blastocysts, and LM rate for hatched blastocysts was 10.3% compared to 10.1% in hatching blastocysts. Limitations, reasons for caution: The limited data set did not include fresh embryo transfers or the transfer of untested embryos. The inclusion of increased embryo numbers could strengthen the power of the evaluation and allow for more robust statistical analysis. Wider implications of the findings: Embryo selection is a multifactorial process consisting of a wide range of parameters. Numerous advances in embryo production and evaluation have resulted in the need for an algorithm or guide to rank embryos for transfer. Further investigation is warranted to elucidate comprehensive recommendations for embryo selection. Trial registration number: not applicable